Blinatumomab in pediatric patients with relapsed/refractory B‐cell precursor acute lymphoblastic leukemia. (11th January 2021) - Queudeville, Manon; Schlegel, Patrick; Heinz, Amadeus T.; Lenz, Teresa; Döring, Michaela; Holzer, Ursula; Hartmann, Ulrike; Kreyenberg, Hermann; von Stackelberg, Arend; Schrappe, Martin; Zugmaier, Gerhard; Feuchtinger, Tobias; et al.
Abstract: Objective: Pediatric patients with relapsed or refractory acute lymphoblastic leukemia have a poor prognosis. We here assess the response rates, adverse events, and long‐term follow‐up of pediatric patients with relapsed/refractory acute lymphoblastic leukemia receiving blinatumomab. Methods: Retrospective analysis of a single‐center experience with blinatumomab in 38 patients over a period of 10 years. Results: The median age at onset of therapy was 10 years (1‐21 years). Seventy‐one percent of patients had undergone at least one hematopoietic stem cell transplantation (HSCT) prior to treatment with blinatumomab. We observed a response to blinatumomab in 13/38 patients (34%). The predominant side effect was febrile reactions, nearly half of the patients developed a cytokine release syndrome. Eight events of neurotoxicity were registered over the 78 cycles (15%). To date, nine patients (24%) are alive and in complete molecular remission. All survivors underwent haploidentical HSCT after treatment with blinatumomab. Conclusions: Despite heavy pretreatment of most of our patients, severe adverse events were rare and response rates encouraging. Blinatumomab is a valuable bridging salvage therapy for relapsed or refractory patients to a second or even third HSCT.